BARTONELLOSIS IN THE STRUCTURE OF VECTOR-BORNE CO-INFECTIONS: PATHOGENETIC AND DIAGNOSTIC ASPECTS - Олійник, Ніна; Кравець, Наталія (SWorldJournal, 2025)
The article examines the role of Bartonella spp. in the structure of vector-borne co-infections. Particular attention is given to the interaction between Bartonella henselae and Borrelia burgdorferi, which may modify the course of Lyme disease, enhance i